The French Integrative Psychosocial Rehabilitation Assessment for Complex Situations (FIPRACS): Modelization of an Adapted Assessment Method Toward Long-Term Psychiatric Inpatients With Disabling, Severe and Persistent Mental Illness - Clesse, Christophe; Salime, S.; Dumand, I.; Concetta-Ciciarelli, S. Barbier; Lavenir, S.; Kacemi, K.; Heckel-Chalet, P.; Sissung, Frank; Poinsignon, Aurore; Simon, Anthony; Decker, M.; Batt, M. (Frontiers in Psychiatry, 2020)
For the past forty years, the generalization of community-based approaches has prompted psychiatry into promoting a deinstitutionalization movement and a psychosocial rehabilitation approach (PSR) for individuals with schizophrenia and related difficulties. Unfortunately, this approach generally does not involve the most severe cognitive and psycho-affective clinical situations among this population despite an increasing number of publications advocating that all individuals should be included in PSR and deinstitutionalization programs. In this context, considering the absence of an assessment battery designed for French individuals with particularly disabling, severe and persistent mental illness (IDSPMI), we constructed an integrative assessment model adapted to this specific population. To select the most suitable tools for this population, a literature review (inspired by the PRISMA protocol) and a systematic review were combined with a clinical assessment study. The literature review first identified the cognitive and psycho-affective functions which mainly influence the day-to-day life adaptation of individuals engaged in a PSR/deinstitutionalization program. The systematic review then gathered all of the useable French validated tools to assess the initially selected dimensions (n=87). To finish, for each dimension, the selected 87 tools were included in a clinical assessment study performed within a French psychiatric hospital. The authors collected and verified the characteristics of each tool (validity, French norms, French version, the average speed of the test, ease of use, ability to assess other dimensions). Their suitability was also assessed when applied to IDSPMI. Based on this final clinical evaluation, the authors selected one tool per function to create the French Integrative Psychosocial Rehabilitation Assessment for Complex Situations (FIPRACS). This battery is an assessment tailored to the neurocognitive and psycho-affective potentials of IDSPMI. While further validation studies of this battery are ultimately required, the practical/clinical implications of this battery are presented and discussed.